Bioceramics. selected, peer reviewed papers from the 25th Symposium and Annual Meeting of the International Society for Ceramics in Medicine (ISCM) November 7-10, 2013, Bucharest, Romania - Antoniac, Iulian; Traistaru, Teodor; Davila, Carol (Key engineering materials, 2014)
Collection of selected, peer reviewed papers from the 25th Symposium and Annual Meeting of the International Society for Ceramics in Medicine (ISCM), November 7-10, 2013, Bucharest, Romania. The 37 papers are grouped as follows: I. Bioceramics Synthesis, Characterization and Testing, II. Bioceramics Applications in Dentistry, III. Bioceramics Applications in Orthopedics.